A REVIEW OF PHYSIO-THERMODYNAMIC FACTOR IN FLUENCING FUEL CONSUMPTION IN INTERNAL COMBUSTION ENGINES FOR AUTOMOTIVE APPLICATION - John, G. R.; Wilson, L. (Tanzania Journal of Engineering and Technology, 2018)
Abstract